HF-Ultrasonography to Quantify Skin Atrophy in Patients with Inflammatory Rheumatic Diseases Treated with Courses of Glucocorticoids - Antonia Schuster; Andreas Horn; Florian Günther; Martin Fleck; Wolfgang Hartung; Boris Ehrenstein (Diagnostics)
Background: Prolonged courses of glucocorticoids (GCs) for patients suffering from inflammatory rheumatic diseases (IRDs) are associated with adverse effects. High-frequency ultrasonography (HFUS) has been utilized to quantify skin changes during short-term topical GC treatment. We aimed to quantify skin atrophy in IRD patients treated systemically with prolonged courses of GCs. Methods: We performed a cross-sectional study comparing patients with IRDs and GC treatment who presented with clinically evident skin atrophy to a matched cohort (1:1) without IRDs and GC treatment. Skinfold measurements, utilizing a standardized caliper, and B-mode HFUS images, utilizing an 18 MHz linear sonography probe, were acquired at back-of-hand, cubital, and dorsal midfoot regions and then compared between both groups. Results: A total of 53 GC-treated IRD patients (33 (62%) women, mean age 66.4 (±10.0) years, GC treatment median 8.0 (1.0–47.0) years) were compared to 53 subjects without IRDs and GC treatment (32 (60%) women, 65.9 (±11.3) years). Skinfold thickness measured at the back of hands [1.7 (±0.4) vs. 2.1 (±0.5) mm, p < 0.001], but not at the cubital [6.7 (±2.7) vs. 7.1 (±3.0) mm] or dorsal midfoot [3.6 (±3.7) vs. 4.1 (±3.4) mm] areas, showed a significant difference between the groups. In comparison, all areas displayed statistically significant different cutaneous thickness in the evaluation by HFUS: hand 0.66 (±0.12) vs. 0.82 (±0.18), p < 0.001; cubital 0.86 (±0.15) vs. 1.00 (±0.21), p < 0.001; and midfoot 0.76 (±0.16) vs. 0.94 (±0.18), p < 0.001. Conclusions: This study revealed significantly lower values in the measured cutaneous thickness by HFUS for GC-treated patients with IRDs compared to persons without IRD and GC treatment.